Changes in the mechanical properties of human hair under various conditions - Boo, Khee Meng. (2010)
This project sought to investigate the tensile properties of human hair when subjected to specific conditions which is hair coloring and exposure to chlorine. Hair samples from 10 individuals of the Chinese population was randomly collected